Anxiety, OCD, delusions, and religiosity among the general public during the COVID‐19 pandemic. Issue 241 (5th July 2021) - Abdullah, Iqra; Parveen, Shazia; Shahid Khan, Nauman; Abdullah, Danyal
Abstract: The COVID‐19 outbreak has not only affected the physical health of the public but also resulted in severe psychological outcomes. This study aims to investigate the psychological effects of the COVID‐19 outbreak on Pakistan's general public. In order to identify the main psychological factors that have emerged due to the current pandemic, extensive literature and opinion pieces of psychologists were reviewed. After a thorough study of the existing scholarship, four main psychological factors were investigated: stress and anxiety, obsessive compulsive disorder (OCD), delusions of getting infected from the disease, and religiosity. A research survey was circulated among the sample population online. A total 356 valid responses were received in the period of two to three weeks. Findings showed that the respondents reported a moderate level of anxiety, occasional symptoms of OCD, and delusions. However, respondents showed a high inclination toward religion during the current pandemic situation. Furthermore, respondents highlighted a few other psychological factors, such as financial strain and loneliness, in the survey. The primary sources of COVID‐19‐related information were social media and television among the general public of Pakistan. Finally, guidelines and tips from the reviewed psychologists and psychiatrists on overcoming the highlighted psychological problems that have arisen due to the COVID‐19 outbreak were summarised.